STUDI PENGARUH KEPEMIMPINAN TRANSFORMASI TERHADAP KINERJA SUMBER DAYA MANUSIA DI PUSKESMAS CAKRANEGARA TAHUN 2024 - Abiburrahman; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Slamet Mardiyanto Rahayu; Fathurrahman; Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2024)
Transformational leadership has a positive and significant effect on human resource performance at the Cakranegara Community Health Center. This is evidenced by a significance value of 0.000 (<0.05) and a regression coefficient value of 0.598, indicating that increasing the application of a transformational leadership style can significantly improve HR performance. Furthermore, the R-Square value of 0.503 indicates that more than half of the variation in HR performance can be explained by this leadership style. The remaining 49.7% is likely influenced by other factors such as intrinsic motivation, work environment, reward system, and individual competence. The higher the level of application of transformational leadership, characterized by inspiration, individual attention, subordinate empowerment, and intellectual stimulation, the higher theemployee performance. This finding reinforces the importance of the role of leaders in creating a productive, supportive, and directed work environment in achieving optimal health service goals at the community health center.